Analisis Mura’ah An-Nadzir : Penerapan Ilmu Badi’ dalam Ayat Al-Qur’an - Ismi Khairani; Masnida Wati Suryani; Harun Al-Rasyid (STIKes Ibnu Sina Ajibarang, 2025)
Mura'ah an-Nadzir is a concept in badi' science which refers to the technique of combining harmonious and appropriate meanings in one expression without containing conflict. This technique plays an important role in creating rhetorical beauty and strengthening the delivery of the message. Through examples from the Qur'an, such as the combination of Allah's attributes in the sentence